Nucleation, growth and transformation of microdefects in FZ-Si - Talanin, V.I.; Talanin, I.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The physical model of microdefects formation in dislocation-free FZ-Si single crystals is offered. Experimental results and theoretical data allows to approve that recombination between vacancy and self-interstitials at high temperatures is hampered by an entropy barrier. Established is that the process of microdefects formation in silicon proceeds simultaneously by two independent mechanisms: the vacancy and interstitial ones.